Analisis Peran Stakeholder Terhadap Kesuksesan Proyek Konstruksi - Zainuddin, Zainuddin; Aulia, Aulia (University of Muhammadiyah Aceh, 2021)
Good management of the project is a prerequisite for achieving project objectives. Every construction company must be able to demonstrate the quality of its services so that it can excel in the competition. The problem in this study is whether the role of stakeholders affects the success of a construction project and how much influence it has on the success of the project. In this study the sample taken was the Department of Housing and Settlements of Banda Aceh City and obtained 6 respondents and PT Coplanar Daya Maxima obtained 4 respondents. Respondents in the purpose of this study were to find out what roles and how much influence stakeholders have on the success of construction projects. Data collection technique is distributing questionnaires to respondents. Data processing was carried out using validity and reliability tests then data analysis using descriptive analysis and product moment correlation, as well as multiple linear regression using SPSS version 25. This study consisted of independent variables (X) consisting of owners (X1), employees (X2), suppliers (X3), consumers (X4), competitors (X5) and business licenses (X6) and the selection variable (Y). The test results for the validity of the r-table value of 0.6319 meet the requirements for r-count > r-table. The results of the reliability test show that all independent variables (X) and stakeholder determinant variables (Y) are reliable. This is because it has met the minimum coefficient of Cronbach Alpha, which is greater than 0.6. The results of descriptive analysis have the lowest mean value found in the employee variable (X2) and business license (X6) of 4.100 and the highest mean value of the supplier variable (X3) of 4.475 which shows that the average respondent's answer is important, then all variables play an important role in project success. construction. The results of multiple linear regression obtained the following equation: Y = 24.018 + 0.412X1 – 0.002X2 – 0.759X3 – 0.526X4 + 0.427X5 – 0.701X6. The analysis shows that the dominant influence of the role of stakeholders on the success of the project is in the supplier variable (X3) with a regression coefficient value of -0.759 and the level of relationship between suppliers (X3) and stakeholders. The results of the classification of the relationship level on the value of the correlation coefficient based on the interval table of the correlation coefficient value and the strength of the relationship.